LEGAL PROBLEMS OF WIREBREAKING REGULATIONS IN THE NEW KUHAP: THE PERSPECTIVE OF DUE PROCESS OF LAW AND PROTECTION OF PRIVACY RIGHTS - Jacelyn Valencia Chiam; Catharina Dewi Wulansari (RADJA PUBLIKA, 2026)
Wiretapping is one of the most effective methods for uncovering crimes, especially those committed in an organized, transnational manner, and utilizing information technology. However, on the other hand, wiretapping is a form of restriction on the right to privacy because it is carried out secretly and allows the state to gain complete access to a person's private communications. The regulation of wiretapping in the New Criminal Procedure Code (KUHAP) through Article 136 is an important development in Indonesian criminal procedure law because it is the first time that wiretapping is recognized as a coercive measure in general criminal procedure law. However, this regulation is still vague and leaves further regulation to separate laws, thus giving rise to various legal problems. This study aims to analyze the legal problems of the regulation of wiretapping in the New KUHAP and formulate a concept for an ideal regulation of wiretapping based on the principles of due process of law and protection of the right to privacy. This study uses a normative legal research method with a statutory approach, a conceptual approach, and a comparative approach. The research results show that Article 136 of the New Criminal Procedure Code still leaves gaps in norms regarding procedures, licensing mechanisms, oversight, the use of wiretapping results, the destruction of irrelevant information, and compensation mechanisms. Therefore, comprehensive wiretapping regulations are needed to achieve a balance between law enforcement and human rights protection.